Sol-gel based Deposition of TixV1-xO Films for Thermally Controlled Optical Switching Applications - Orawan Tanomkiat; Chokchai Kahattha; Wisanu Pecharapa; Wichan Techitdheera (My University, 2011)
Abstract Ternary thermochromic TixV1-xO thin films were successfully fabricated by sol-gel precursor based on vanadium acetylacetonate, titanium butoxide, absolute ethanol and deionized water. All films were deposited by spin coating technique and post-annealed at 500 °C for 2 hr. The effect of titanium consolidation on the structural, surface morphology and optical properties of these films were investigated by X-ray diffraction (XRD), Atomic force spectroscopy (AFM) and UV-VIS spectroscopy, respectively. The XRD patterns evidently reflect peak orientation planes of vanadium oxide. The surface morphology and surface roughness of the films changed with increased titanium concentration seen in AFM profiles. The optical band gap of the film is increased when titanium composition increases. The certain content of titanium significantly affects the film thermochromic properties.
Keywords: Deposition; Transition Metal Oxide Nanomaterials